Design and modeling of SMES based SAPF for pulsed power load demands. (November 2017) - Panda, Anup Kumar; Penthia, Trilochan
Highlights: Design and modelling of the SMES based SAPF have been presented. The efficacy of the SMES based SAPF over conventional SAPF has been demonstrated. A modified synchronous reference frame (MSRF) technique is proposed in the system. Active and reactive power compensation by the SMES based SAPF is analyzed. Abstract: In this article, a Superconducting Magnetic Energy Storage (SMES) based Shunt Active Power Filter (SAPF) topology is proposed to compensate high power pulsating load demands in a power system. The SMES based SAPF is designed and modeled to realize as an efficient compensator for the compensation of pulsed power load demands. The conventional SAPF is efficient to mitigate the power quality problems in a power system unless there is high power pulsating load demands, transient conditions or power fluctuations. Particularly, a Modified Synchronous Reference Frame (MSRF) control algorithm has been implemented to generate proper switching signals for the three-phase Voltage Source Converter (VSC) of the SMES based SAPF. In the simulation, it has been seen that the SAPF is incompetent under high power pulsating load demands whereas the SMES based SAPF has shown excellent performance under such load conditions. Moreover, a comparative analysis has been made between the conventional SAPF and the SMES based SAPF under pulsating load conditions, to check the effectiveness of the SMES based SAPF. The performance of the proposed system is presented by using Sim Power System (SPS)/MATLAB Simulink and real-time digital simulator laboratory (RTDS-Lab).